The Impact of Stigma on the Mental Health of Adolescents with Tuberculosis: A Scoping Review - Muhamad Nuryanto; Nur Setiawati Dewi; Megah Andriany (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stigma toward adolescents with tuberculosis (TB) is a significant psychosocial issue that negatively affects their mental health. Adolescents are emotionally vulnerable, and the experience of stigma can exacerbate psychological distress and hinder treatment adherence. Objective: This study aims to review the scientific literature on the impact of stigma on the mental health of adolescents with tuberculosis and to identify the affected domains of mental well-being. Method: A scoping review was conducted in accordance with the PRISMA-ScR guidelines. Literature searches were performed in three major databases (Scopus, PubMed, and ScienceDirect) using the keywords “stigma,” “tuberculosis,” and “adolescent.” Articles were selected based on inclusion criteria: published between 2021 and 2025, written in english, open access, and directly relevant to the research, data extraction from the selected articles was conducted using a matrix format in microsoft word. The domains used for data extraction included the researcher’s name and year of publication, article title, research objectives, research methodology, research instruments, and key findings. Results: Out of 1,233 initially retrieved articles, 10 met the eligibility criteria and were analyzed. The synthesis of findings revealed that stigma has a detrimental impact on adolescent mental health, particularly in the forms of anxiety, depression, social withdrawal, and feelings of hopelessness. Stigma was also identified as a contributing factor to poor treatment adherence among adolescents with TB. Stigma significantly contributes to mental health challenges in adolescents diagnosed with tuberculosis. These findings highlight the urgent need for the development of multidisciplinary interventions that address psychosocial aspects to support treatment success and enhance the quality of life among adolescent TB patients.